Environmental DNA for assessing abundance of salmon lice (Lepeophtheirus salmonis) in salmon (Salmo salar) farms - Nygaard, Magnus (UiT The Arctic University of Norway, 2018)
The aim of this thesis was to investigate an alternative way to detect salmon lice (Lepeophtheirus salmonis) in the field, and investigate the possibility of counting salmon lice in a commercial farming facility of Atlantic salmon (Salmo salar) by using methods and tools based on environmental DNA (henceforth referred to as eDNA). This was performed by sampling water in a salmon farming facility over a couple of months, collecting live salmon lice at a local salmon slaughter factory and conducting an experiment in a laboratory under a controlled environment.